New insights into immunomodulatory properties of lactic acid bacteria fermented herbal medicines - Zhu, Hongru; Guo, Lidong; Yu, Dan; Du, Xiaowei (Frontiers in Microbiology, 2022)
The COVID-19 pandemic has brought more attention to the immune system, the body’s defense against infectious diseases. The immunomodulatory ability of traditional herbal medicine has been confirmed through clinical trial research, and has obvious advantages over prescription drugs due to its high number of potential targets and low toxicity. The active compounds of herbal drugs primarily include polysaccharides, saponins, flavonoids, and phenolics and can be modified to produce new active compounds after lactic acid bacteria (LAB) fermentation. LAB, primary source of probiotics, can produce additional immunomodulatory metabolites such as exopolysaccharides, short-chain fatty acids, and bacteriocins. Moreover, several compounds from herbal medicines can promote the growth and production of LAB-based immune active metabolites. Thus, LAB-mediated fermentation of herbal medicines has become a novel strategy for regulating human immune responses. The current review discusses the immunomodulatory properties and active compounds of LAB fermented herbal drugs, the interaction between LAB and herbal medicines, and changes in immunoregulatory components that occur during fermentation. This study also discusses the mechanisms by which LAB-fermented herbal medicines regulate the immune response, including activation of the innate or adaptive immune system and the maintenance of intestinal immune homeostasis.